Theoretical Investigation of the Adsorption and C-C Bond Scission of CCH3 on the (111) and (100) Surfaces of Pd: Comparison with Pt - Kim, Seok Ki; Shin, Jungho; Moon, Sang Heup; Kim, Jaehoon; Lee, Seung-Cheol (American Chemical Society, 2013)
Understanding the mechanism of C-C bond cleavage on the surface of a catalyst is central to the optimization of several reactions in the petrochemical industry. In this study, first-principles density functional theory calculations were performed to examine the adsorption properties, electronic structures, and energies of C-C bond scission in ethylidyne (CCH3) adsorbed on the (111) and (100) surfaces of Pd, and the results were compared with those of Pt. On the basis of the analyses of the electron density of states (DOS), partial charge density, and wave functions, it appears that on the adsorption of C-C, two types of bonding orbitals, namely, sigma(C-C) and pi(C-C), are formed. On both the low-index surfaces of Pd, the perpendicular adsorption of CCH3 was found to be the most stable configuration. Compared with the adsorption on the Pd( 111) surface, the adsorption on the Pd(100) surface was less stable. On the contrary, the adsorption energies on the (111) and (100) surfaces of Pt were almost the same. Nevertheless, in both Pd and Pt, the C-C bond scission energy on the (111) surface was higher than that on the (100) surface because the hybridization of atomic carbon was more stable.
Keywords: ACETYLENE-ETHYLENE MIXTURES; TOTAL-ENERGY CALCULATIONS; SUM-FREQUENCY GENERATION; SINGLE-CRYSTAL SURFACES; AUGMENTED-WAVE METHOD; KINETIC MONTE-CARLO; ETHANE HYDROGENOLYSIS; STRUCTURE SENSITIVITY; CATALYTIC-REACTIONS; METAL-SURFACES